Coordination Demands of International Strategies - Martinez, Jon I.; Jarillo, J. Carlos (Journal of International Business Studies, 1991)
A study of fifty subsidiaries of Multinational Corporations shows a connection between their strategy and their use of different mechanisms of coordination. The main finding is that subsidiaries pursuing strategies with a high degree of integration with their corporate parent make a much more extensive use of both “formal” and “subtle” coordination mechanisms than other firms in the sample. These results are borne out in both static and dynamic tests. They confirm previous literature on coordination mechanisms in organizations in general and apply that literature to the field of multinational corporations, which are some of today's more important and complex business organizations.